Relationship between peer-to-peer lending model improvement and customer satisfaction for company reputation - Fasha, Muhamamd Aderaka; Soma, AM; Sitorus, Palti Marulitua (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2025)
This research examines the importance of company reputation for business growth, sustainability and success, because corporate reputation is an intangible asset for the management of all companies. Facing the challenges posed by the traditional banking system, SMEs are often prevented from obtaining the financing they need to grow and develop. This research aims to analyze the relationship between improving the peer-to-peer (P2P) lending model and customer satisfaction in order to maintain the company's reputation, with a case study at PT Amartha. Through a quantitative analysis approach, this research uses measurements that utilize a Likert scale with the population being users of the Amartha Peer to Peer (P2P) lending platform. This research uses the Structural Equation Modeling (SEM) data analysis method processed with SmartPLS. Based on the analysis carried out, the findings in this research show that operational efficiency, service innovation and process speed have a positive effect on the company's reputation. Apart from that, it is hoped that PT Amartha will continue to maintain customer satisfaction by adding new innovations or breakthroughs and improving service performance so that satisfaction levels increase and encourage a good company reputation.